2015
DOI: 10.1111/1750-3841.12819
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Visual Characteristics of Whipped Cream by Image Analysis and Machine Vision: Method Development

Abstract: The appearance (color, shine, surface roughness, bumpiness, view area, height) of whipped cream samples change with time. Quantitative methods based on image analysis were developed to measure these parameters in cream samples stored at 3 temperatures (room temperature, 10 °C and 2 °C) for up to 24 h. There was a small decrease in L* and a* values over time, and a significant increase in b* values. ΔE values suggest that these color changes are significant and observable (2.96 for room temperature, 9.46 for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Colorimeters and spectrophotometers only show the average value of the testing region, and obtain quite unrepresentative results and restrict global analysis . Recently, computer vision‐based image analysis systems and machine vision have been used to objectively measure the surface colour of various products, since they can provide some obvious advantages because of their objectivity and quantitative capabilities . The visual characteristics obtained by computer vision‐based image analysis systems include colour, shine, surface roughness, bumpiness, view area and height .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colorimeters and spectrophotometers only show the average value of the testing region, and obtain quite unrepresentative results and restrict global analysis . Recently, computer vision‐based image analysis systems and machine vision have been used to objectively measure the surface colour of various products, since they can provide some obvious advantages because of their objectivity and quantitative capabilities . The visual characteristics obtained by computer vision‐based image analysis systems include colour, shine, surface roughness, bumpiness, view area and height .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, computer vision‐based image analysis systems and machine vision have been used to objectively measure the surface colour of various products, since they can provide some obvious advantages because of their objectivity and quantitative capabilities . The visual characteristics obtained by computer vision‐based image analysis systems include colour, shine, surface roughness, bumpiness, view area and height . The system commonly is mainly composed of the illuminant, a digital camera, digitizer and software to analysis the pictures, and two processes – image acquisition and image processing – are usually carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the 1% whipped cream variant showed significantly higher values of a* and b* compared to the 0.1% whipped cream variant and control (with no encapsulant addition). The increase in b* values indicated the yellowish color of the samples [28]. This could be due to the golden-brown color of the spray-dried encapsulant spiked at 1% in the whipped cream.…”
Section: Effect Of the Wph-md-encapsulated Probiotics Formulation On ...mentioning
confidence: 97%